Forms Of Education Of Moderns In Schools - Akhmadjonova Gulnoza (Global Scientific Publishing, 2024)
This article analyzes Mahmudhoja Behbudi, Jadidism, Jadid schools, and the activities of enlightened scientists, sciences
Keywords: Turkestan; jadidism; colonial policy